Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Financial Distress Model Altman Z- Score pada Sektor Consumer Cyclicals di Indonesia - Putri Nur Hasanah; Muhammad Iqbal Pribadi; Rahman Anshari (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to examine the influence of profitability and firm size on financial distress in companies operating within the consumer cyclicals sector listed on the Indonesia Stock Exchange during the 2021–2023 period. Financial distress was assessed using the Altman Z-Score model. A quantitative approach was employed, utilizing purposive sampling to select a final sample of 101 companies. The analysis was conducted using panel data regression with a fixed effect model. The results indicate that profitability has a positive and statistically significant effect on financial distress , while firm size exerts a negative and significant influence. These findings suggest that companies with higher profitability are generally more resilient to financial distress , whereas larger firms may still be exposed to financial vulnerabilities if not managed effectively.